ASSESSMENT OF WATER QUALITY (PHYSICO-CHEMICAL) OF KANEKAL TANK, ANANTAPURAMU DIST., AP, INDIA. - GUNDALA, PHILIP HAROLD; V N, JAYARAM NAIK; KOLALA, VENKATA RAMANAIAH (Journal of Experimental Sciences)
Abstract: Different Physico-chemical parameters of Kanekal tank water, Kanekal were estimated from October 2012 to September 2014 to assess its quality. The different parameters like Temperature, pH, TDS, conductivity, salinity, dissolved oxygen, turbidity, alkalinity, free carbon dioxide, chloride, total hardness, calcium, magnesium, phosphates, sulphates, silicates, nitrites, nitrates, BOD and COD were carried out by standard methods. These parameters showed either positive or negative correlation between each other. The analysis revels these parameters are interrelated with each other. From the data it can be said that water of this tank is partially contaminated with human faeces, domestic sewage etc. Hence it is not good quality for culture of fish as well as drinking for animals. KeywordsÂ â€“Kanekal Tank, water quality, Physico-chemical parameters, BOD, COD